DAMPAK LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PNS DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA KANTOR BAPENDA KABUPATEN BANYUWANGI - Yulianingtiyas, Liana; Ediyanto, Ediyanto; Minullah, Minullah (Fakultas Ekonomi dan Bisnis, 2023)
Humans Regional Revenue Office of Banyuwangi is an organization of government apparatus with a good reputation as implementing element in government, community and development sectors led by the head of department who is responsible to Regent through Regional Secretary. The purpose of this study is to analyze the effect of work environment and work discipline on performance with Job Satisfaction as an intervening variable at Regional Revenue Office of Banyuwangi by using Partial Least Square – Structural Equation Modeling (PLS-SEM). The results of direct effect hypothesis testing using Smart PLS 3.0 application show that work environment has a significant positive effect on job satisfaction (H1 is accepted), work discipline has a significant positive effect on job satisfaction (H2 is accepted), work environment has a significant positive effect on performance (H3 is accepted), work discipline has a negative and not significant effect on performance (H4 is rejected), job satisfaction has a significant positive effect on performance (H5 is accepted), work environment has a significant positive effect on performance through job satisfaction (H6 is accepted), work discipline has a positive but not significant effect on performance through satisfaction Work (H7 is rejected).